Prothrombin and Its Derivatives Stimulate Motility of Melanoma Cells - Zhou, Hong; Gabazza, Esteban C.; Takeya, Hiroyuki; Deguchi, Hiroshi; Urano, Hajime; Adachi, Yukihiko; Suzuki, Koji (Thrombosis and Haemostasis, 1998)
Several studies indicated that activation of the clotting system may promote the growth and the invasive behavior of tumor cells. In the present study, we evaluated the migratory response of various melanoma cell lines to several clotting factors and prothrombin derivatives (thrombin, fragment 1, fragment 2 and kringle 1 fragment). Prothrombin, thrombin and fragment 1 stimulated chemotaxis of the murine (K-1735 M2, X21) and human A375 (SM) melanoma cell lines. Prothrombin and prothrombin fragment 1 showed their maximal chemo-tactic activity at 0.5~1 μM. Chemotaxis induced by thrombin was inhibited by hirudin, but not that induced by prothrombin or fragment 1. Other clotting proteins and the fragment 2 and kringle 1 fragment of prothrombin did not elicit chemotactic activity. Checkerboard analysis indicated that motility was directional with a significant chemokinetic component. The K-1735 M2 cells also migrated in a concentration-dependent manner to substratum-bound insoluble prothrombin, thrombin or fragment 1. Ligand binding assays showed that both prothrombin and fragment 1 bound to K-1735 M2 cells with apparent Kds of 0.5 μM. This binding was inhibited by an excess concentration of unlabeled prothrombin and fragment 1 but not by similar concentrations of other prothrombin fragments. These findings suggest that prothrombin and its fragment 1 exert chemotactic activity on melanoma cells by different mechanisms and different binding sites from that induced by thrombin.